Acetylated deoxycholic (DCA) and cholic (CA) acids are potent ligands of pregnane X (PXR) receptor. (4th January 2017) - Carazo, Alejandro; Hyrsova, Lucie; Dusek, Jan; Chodounska, Hana; Horvatova, Alzbeta; Berka, Karel; Bazgier, Vaclav; Gan-Schreier, Hongying; Chamulitrat, Waleé; Kudova, Eva; Pavek, Petr
Graphical abstract: Highlights: Acetylated deoxycholic (DCA) and cholic (CA) acids are potent ligands of PXR. Acetylated DCA and CA enhance PXR target genes expression. Dehydrogenation or acetylation of DCA, CA, lithocholic (LCA) or chenodeoxycholic (CDCA) do not lead to increased affinity to FXR or VDR. Acetylated DCA and CA were not found in bile. Abstract: The Pregnane X (PXR), Vitamin D (VDR) and Farnesoid X (FXR) nuclear receptors have been shown to be receptors of bile acids controlling their detoxification or synthesis. Chenodeoxycholic (CDCA) and lithocholic (LCA) acids are ligands of FXR and VDR, respectively, whereas 3-keto and acetylated derivates of LCA have been described as ligands for all three receptors. In this study, we hypothesized that oxidation or acetylation at position 3, 7 and 12 of bile acids DCA (deoxycholic acid), LCA, CA (cholic acid), and CDCA by detoxification enzymes or microbiome may have an effect on the interactions with bile acid nuclear receptors. We employed reporter gene assays in HepG2 cells, the TR-FRET assay with recombinant PXR and RT-PCR to study the effects of acetylated and keto bile acids on the nuclear receptors activation and their target gene expression in differentiated hepatic HepaRG cells. We demonstrate that the DCA 3, 12-diacetate and CA 3, 7, 12-triacetate derivatives are ligands of PXR and DCA 3, 12-diacetate induces PXR target genes such as CYP3A4, CYP2B6 and ABCB1/MDR1. In conclusion, we found that acetylated DCA and CA are potent ligands of PXR. Whether the acetylated bile acid derivatives are novel endogenous ligands of PXR with detoxification or physiological functions should be further studied in ongoing experiments.